D(A-A′)2 architecture: An efficient strategy to improve photovoltaic performance of small molecules for solution-processed organic solar cells. (October 2016) - Tao, Qiang; Duan, Linrui; Xiong, Wenjing; Huang, Gongyue; Wang, Pu; Tan, Hua; Wang, Yafei; Yang, Renqiang; Zhu, Weiguo
Abstract: Two novel small molecules (SMs) of BDT(TPD-DPP)2 and BDTT(TPD-DPP)2 with a D(A-A′)2 framework were designed and synthesized, in which the electron-rich benzodithiophene (BDT) and thiophenyl-substituted benzodithiophene (BDTT) are used as a central donor (D) core, as well as the electron-deficient diketopyrrolopyrrole (DPP) and thieno [3, 4-c]pyrrole-4, 6-dione (TPD) as dual acceptor (A and A′) units, respectively. Their optical, electrochemical, and photovoltaic properties were investigated together with their counterparts, which bearing an accepter-donor-accepter (A-D-A) architecture. Wider and stronger solar photon responses and decreasing the lowest unoccupied orbital (LUMO) levels are observed in the D(A-A′)2 rather than A-D-A type SMs. The significantly increasing power conversion efficiency of 4.25% with a short-circuit current density of 10.08 mA cm −2 were obtained in the BDTT(TPD-DPP)2 based solar cells. This work demonstrates that using D(A-A′)2 architecture with dual acceptor units is an effective method to improve photovoltaic performance of SMs for solution-processed organic solar cells. Graphical abstract: Two novel small molecules (SMs) of BDT(TPD-DPP)2 and BDTT(TPD-DPP)2 with a D(A-A′)2 framework were obtained on the basis of the A-D-A type SMs. Significantly improved photovoltaic properties with a power conversion efficiency of 4.25% and a short-circuit current density of 10.08 mA cm −2 were obtained in the D(A-A′)2 type SMs. Highlights: Two SMs of BDT(TPD-DPP)2 and BDTT(TPD-DPP)2 with a D(A-A′)2 framework are prepared. Both SMs exhibit wider absorption and deeper LUMO energy levels than A-D-A type SMs. The BDTT(TPD-DPP)2 based device presents a significantly increasing PCE of 4.25%.